Effect of dietary supplementation with different level of lycopene in fertility, hatchability traits and concentrations of estrogen and proges-terone hormones in serum of Iraqi local geese. - عباس الجنابي يحيى; خضير ثامر كريم; نوري الياسري احمد; مرزه سهيل سلام (Journal of Kerbala for Agricultural Sciences, 2017)
This study has been conducted at the poultry farm for department of Animal Resource, College of Agriculture at University of Baghdad during the period from 20/10/2013 to 28/3/2014. The aim of this study was to investigate the effect of dietary supplementation with different level of lycopene in fertility and hatchability from fertilize eggs, hatchability from set eggs, embryonic mortality and concentrations of estrogen and progesterone hormones in serum of local Iraqi geese. A total of 48 local geese females two years old were used in this study. The geese were randomly distributed in to four treatments groups, each group consisted of 12 birds. Birds were fed during the whole period on diet contain 15% crude protein and 2950 Kcal metabolic energy / kg. Lycopene was added to the diets of birds at the beginning till the end of experiment period. The birds were reared in single separated cages during the experiment period. groups were as following: Treatment 1 (T1) birds fed diet without any addition of lycopene (control group) , Treatment 2 (T2) birds fed diet supplemented with 300 mg lycopene / Kg of diet, Treatment 3 (T3) birds fed diet supplemented with 600 mg lycopene / Kg of diet, Treatment 4 (T4) birds fed diet supplemented with 900 mg lycopene / Kg of diet. Results revealed that dietary supplementation with different levels of lycopene resulted in Significant improvement with respect to percentages of fertility and hatchability from fertilize eggs, hatchability from set eggs and embryonic mortality as compared with control group. Significant increase in serum concentrations of estrogen and progesterone hormones in compared with control group.